P13 Penicillin allergy de-labelling in a sexual health clinic. (16th June 2022) - Boylan, Johnny; Leighton, Jennifer; Alachkar, Hana
Abstract : Introduction: Penicillin allergy (PA) is self-reported in approximately 10% of people. Reported allergic reactions to penicillin range from mild to severe (including anaphylaxis) and limit treatment options for some sexually transmitted infections. Often the allergy label is given in childhood and less than 10% of those who report allergy are truly allergic. We discuss the development of a PA de-labelling pathway for use in sexual health clinics (SHC). Methods: We preformed a retrospective review of patients who underwent PA de-labelling within the SHC. Data regarding diagnosis, allergy testing outcomes and subsequent treatment was collected. We identified patients appropriate for penicillin challenge via comprehensive allergy history-taking and discussion with tertiary immunology colleagues. We developed a local PA de-labelling protocol for use in SHCs and patient information leaflets to facilitate informed consent for the process. Results: Three patients (two with syphilis in pregnancy and one with multi-drug resistant pharyngeal gonorrhoea) with self-reported PA underwent safe and successful antibiotic challenge within the SHC. Following PA de-labelling, one pregnant patient with syphilis received benzathine penicillin while another received IV ceftriaxone as an outpatient (severe needle-phobia precluded IM injection with penicillin). The patient with multi-drug resistant gonorrhoea and a history of penicillin anaphylaxis also safely received ceftriaxone. Discussion: We demonstrated this process can be safely carried out within SHCs. The risk of the challenge includes life-threatening anaphylaxis (although this is extremely rare) therefore informed consent must be obtained to safely de-label patients with allergy, provide optimal treatment, and avoid inpatient admission for intravenous antibiotics during the pandemic.